Investigation of machinability characteristics and comparative analysis under different machining conditions for sustainable manufacturing. (15th March 2020) - Venkatesan, K.; Devendiran, S.; Sachin, D.; Swaraj, J.
Graphical abstract: Highlights: Turning of Nimonic 90 using dry (PVD, CVD) and MQL (PVD, CVD) condition. Study of force, roughness, tool wear, tool wear mechanism, and chip morphology. Nano lubricant – MQL with hBN for sustainable machining. The effect of machining parameters on selected responses has been investigated. Sustainable improvement has been achieved using nMQL CVD compared to other conditions. Abstract: The study is focussed on the comparative performance of input-parameters on cutting force, roughness, tool wear, and chip morphology of sustainable conditions (dry and MQL: Minimum quantity lubrication) on Nimonic 90 alloy. 0.25 wt% of nano hexagonal boron nitride (hBN) mixed with groundnut oil is used as nanofluids, and experimentations are accomplished on Taguchi's L16 orthogonal array. Results show that in nano-MQL, the improvement of 1.654 and 1.276 times, 4.522, and 2.196 times that dry with two coated carbide insert for force and roughness. Coating loss occurred under the nano-MQL mode, whereas abrasion, notching observed in dry machining. The chip thickness ratio were1.34 times and 1.77 times, the shear angle was 1.22 times and 1.61 times, and reduced coefficient of friction under nano-MQL compared to dry. Nano-MQL with chemical vapour deposition (CVD) carbide insert is suitable for machining of alloy 90 with improved performance characteristics that of other machining conditions.